IMPROVEMENT OF THE CURRENT ASSET MANAGEMENT MECHANISM AS A CONDITION FOR THE EFFECTIVE FUNCTIONING OF ENTERPRISES - GAVATIUK, LIUDMYLA; PILAT, ALONA (Herald of Khmelnytskyi National University. Economic sciences, 2022)
The article analyzes the improvement of the mechanism of current asset management in enterprises as a condition for their effective functioning.Current asset management is a purposeful activity of an enterprise related to determining the amount of current assets, the risk of losses received as a result of a shortage of certain components of current assets, as well as related to control over their formation, use and creation of appropriate organizational prerequisites. The process of improving the mechanism of current asset management of enterprises should include the following stages: analysis of the total volume, composition, structure and efficiency of using current assets in the previous period, selection of the type of current asset formation policy, justification of the quantitative characteristics of the formulated goals, ensuring the optimal volume of all types of current assets, ensuring the optimal ratio of constant and variable parts of current assets, ensuring the necessary level of liquidity and speed of turnover of current assets, ensuring the necessary level of profitability and acceptable level of risk of current assets, selecting forms and sources of financing current assets, monitoring and controlling the current state of current assets and making appropriate corrective decisions.Improving the current asset management mechanism of the enterprise will allow managers to use it to ensure stable functioning and predict the development of the enterprise in the future. If the financial and economic mechanism of current asset management is improved, it will be possible to achieve long-term goals, as well as increase the level of competitiveness of the enterprise in the market.
Keywords: current assets; current asset management; current asset management system; current asset management mechanism; efficiency of current asset management